2019
DOI: 10.1371/journal.pone.0215804
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intellectual and developmental disabilities among first generation adult newcomers, and the health and health service use of this group: A retrospective cohort study

Abstract: Background Attention to research and planning are increasingly being devoted to newcomer health, but the needs of newcomers with disabilities remain largely unknown. This information is difficult to determine since population-level data are rarely available on newcomers or on people with intellectual and developmental disabilities (IDD), although in Ontario, Canada these databases are accessible. This study compared the prevalence of IDD among first generation adult newcomers to adult non-newcomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The only other population-based study that used linked population data from health, social services and immigration found that newcomers with intellectual and developmental disabilities were less healthy and used more services than newcomers with no intellectual and developmental disabilities (Durbin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The only other population-based study that used linked population data from health, social services and immigration found that newcomers with intellectual and developmental disabilities were less healthy and used more services than newcomers with no intellectual and developmental disabilities (Durbin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our prior work based on population data showed that newcomers with IDD have higher rates of health issues than non‐newcomers (Durbin et al, 2019). This only tells part of the story.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations